Fluorescence endoscopy for the detection of low and high grade dysplasia in ulcerative colitis using systemic or local 5-aminolaevulinic acid sensitisation. (1st July 2003) - Messmann, H; Endlicher, E; Freunek, G; Rümmele, P; Schölmerich, J; Knüchel, R
Abstract : Background and aims: Longstanding ulcerative colitis (UC), especially in the presence of epithelial dysplasia, is associated with an increased risk of developing cancer. As dysplasia is not visible during routine endoscopy, at least 40–50 random biopsies in four quadrants every 10 cm are recommended. Fluorescence endoscopy after sensitisation with 5-aminolaevulinic acid (5-ALA) was assessed for the detection of dysplasia in ulcerative colitis by taking optical guided biopsies. 5-ALA is converted intracellularly into the sensitiser protoporphyrin IX which accumulates selectively in neoplastic tissue allowing the detection of dysplasia by typical red fluorescence after illumination with blue light. Methods: In 37 patients with UC, 54 examinations were performed with fluorescence endoscopy after oral (20 mg/kg) or local (either with an enema or by spraying the mucosa with a catheter) sensitisation with 5-ALA. A total of 481 biopsies of red fluorescent (n=218) and non-fluorescent (n=263) areas of the colonic mucosa were taken. Results: Forty two biopsies in 12 patients revealed either low grade (n=40) or high grade (n=2) dysplasia. Sensitivity of fluorescence for dysplastic lesions was excellent and ranged from 87% (95% confidence interval (CI) 0.73–1.00) to 100% (95% CI 1.00–1.00) after local sensitisation, in contrast with only 43% (95% CI 0.17–0.69) after systemic administration. Specificity did not differ for both forms of local sensitisation (enema 51% (95% CI 0.44–0.57) and spray catheter 62% (95% CI 0.51–0.73)); after systemic sensitisation specificity was 73% (95% CI 0.69–0.83). Negative predictive values of non-fluorescent mucosa for exclusion of dysplasia were very high; 89% after systemic sensitisation and 98–100% after local sensitisation. Positive predictive values were 13% and 14% after local sensitisation with enema and spray catheter, and 21% after oral sensitisation with 20 mg/kg ALA. The overall number of biopsies per examination was less than five from fluorescent positive areas. Conclusion: Fluorescence endoscopy after 5-ALA sensitisation is a possible tool to visualise dysplastic lesions in ulcerative colitis using 5-ALA sensitisation. Local sensitisation is a promising alternative approach compared with systemic administration of 5-ALA. A randomised controlled study is now indicated to compare the efficacy of endoscopic fluorescence detection with the standard technique of four quadrant random biopsies.